Age-dependent effect of susceptibility factors on the risk of intracerebral haemorrhage: Multicenter Study on Cerebral Hemorrhage in Italy (MUCH-Italy). Issue 10 (12th July 2021) - Locatelli, Martina; Grassi, Mario; Saba, Valentina; Iacovello, Licia; di Castelnuovo, Augusto; de Gaetano, Giovanni; Zedde, Marialuisa; Marcheselli, Simona; silvestrelli, Giorgio; Ciccone, Alfonso; Delodovici, Maria Luisa; Princiotta Cariddi, Lucia; et al.
Abstract : Objective: To investigate the age-dependent impact of traditional stroke risk factors on the occurrence of intracerebral haemorrhage (ICH). Methods: We performed a case–control analysis, comparing consecutive patients with ICH with age-matched and sex-matched stroke-free controls, enrolled in the setting of the Multicenter Study on Cerebral Hemorrhage in Italy (MUCH-Italy) between 2002 and 2014 by multivariable logistic regression model within subgroups stratified by age quartiles (Q1–Q4). Results: We analysed 3492 patients and 3492 controls. The impact of untreated hypertension on the risk of ICH was higher in the lower than in the upper age quartile (OR 11.64, 95% CI 7.68 to 17.63 in Q1 vs OR 6.05, 95% CI 3.09 to 11.85 in Q4 with intermediate ORs in Q2 and Q3), while the opposite trend was observed for untreated hypercholesterolaemia (OR 0.63, 95% CI 0.45 to 0.97 in Q1 vs OR 0.36, 95% CI 0.26 to 0.56 in Q4 with intermediate ORs in Q2 and Q3). The effect of untreated diabetes and excessive alcohol intake was detected only in the older age group (OR 3.63, 95% CI 1.22 to 10.73, and OR 1.69, 95% CI 1.13 to 2.51, respectively). Conclusions: Our findings provide evidence of age-dependent differences in the effects of susceptibility factors on the risk of ICH.